Pelatihan Pembuatan Batik Jumput Untuk Menumbuhkan Minat Berwirausaha Siswa Di SMAN 1 Kalitidu Bojonegoro - Dinaloni, Diah; Muktiadji, Henky; Indrawati, Indrawati (CV. IRA PUBLISHING, 2024)
SMAN 1 Kalitidu is a school in Wotangare Village, Kalitidu District, Bojonegoro Regency. Based on a survey, approximately 35% to 40% of its graduates can continue their education at higher education institutions. Most of the remaining graduates choose to work due to economic constraints that hinder their ability to pursue further studies. This Community Service Program (PkM) aims to provide tie-dye batik training to foster entrepreneurial interest among students of SMAN 1 Kalitidu Bojonegoro. The implementation method consists of three stages: (1) preparation, involving coordination with the school regarding the schedule, targets, and requirements for the training, as well as preparing materials and tools for tie-dye batik making; (2) execution, carried out through tutorials and hands-on practice; and (3) evaluation, involving the distribution of questionnaires to participants to measure program success based on predetermined indicators. The training was held on December 6, 2024, attended by 25 tenth-grade students. After the tutorial session, participants practiced making tie-dye batik under the guidance of the PCM team. Evaluation results indicated that the training successfully increased students' entrepreneurial interest.